Integrating Mixed Methods Paradigms for Research Gap Identification in Islamic Education Research - Gucandra, Yudi; Sesmiarni, Sesmiarni (El-Rusyd, 2025)
The phenomenon of weak problem identification and research gap analysis in Islamic Education studies reflects a serious epistemological challenge within the academic environment. Many student and faculty research projects remain repetitive and lack strong theoretical and empirical grounding. This article aims to examine the epistemological differences between quantitative and qualitative paradigms in the process of identifying research gaps and to integrate both within the methodology of Islamic Education research. The study employs a qualitative method using a conceptual Systematic Literature Review (SLR) by reviewing scientific articles indexed in Scopus and SINTA from 2020 to 2025. The data were analyzed through narrative and comparative synthesis focusing on ontological, epistemological, and methodological dimensions. The findings indicate that the quantitative paradigm is oriented toward theoretical verification (gap of extension and conflict), whereas the qualitative paradigm emphasizes meaning exploration (gap of void and emergent meaning). The integration of both paradigms produces the Epistemological Gap Framework (EGF), a conceptual model that combines the logic of verification and exploration in formulating research gaps in Islamic Education. This model is expected to strengthen methodological rigor, enhance epistemological awareness, and enrich the scholarly contribution to the development of Islamic Education as a scientific discipline.